RESOCIALIZING EFFECT OF PIMOZIDE ON CHRONIC INSTITUTIONALIZED SCHIZOPHRENIC PATIENTS - Soebagyo Hadinoto, Soebagyo Hadinoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1976)
A clinical trial of pimozide has been conducted, on 20 chronic institutionalized schizophrenic patients. using the "same subject design". The aim was to check the resocializing effect of pimozide such as reported in same papers.A psychotest was constructed to obtain quantitative data concerning obedience and cooperativeness to do a task, work and work capacity. The quantitative data obtained were supplemented with the data observed qualitatively by the experimenting team.The effect of pimozide appeared to be positive and significant with minimal side effect